2014
DOI: 10.1007/s00449-014-1144-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural antioxidants on the lipase activity in the course of batch and continuous glycerolysis of babassu oil

Abstract: The effects of several natural antioxidants (copaiba oil, buriti oil, cocoa butter, tucuman butter, oregano and white thyme) were assessed in the enzymatic synthesis of monoglycerides (MAG) from the glycerolysis of babassu oil. The reactions were catalyzed by Burkholderia cepacia lipase immobilized on SiO2-PVA and the assays carried out in batch and continuous runs. Results were compared with those attained in the control reactions (without any strategy to avoid oxidation), and the best approach was tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, free copaiba oil and nanocapsules also improved RV antioxidant parameters. Previous studies have shown that copaiba oil possesses antioxidant properties 43 and exerts a protective effect against liver injury. 3,44 However, there have not been any studies documenting the activity of copaiba oil in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, free copaiba oil and nanocapsules also improved RV antioxidant parameters. Previous studies have shown that copaiba oil possesses antioxidant properties 43 and exerts a protective effect against liver injury. 3,44 However, there have not been any studies documenting the activity of copaiba oil in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of the MAG product remained stable even after 192 h of continuous operation (6 h for each reaction), 32 consecutive cycles. 62 Production of DAG using immobilized SMG1-F278N was conducted in a packed bed reactor on a pilot-plant scale. The selection of the noncommercial enzyme was due to its excellent esterification yield and reusability in deacidification of high-acid oils and fats reported in previous studies.…”
Section: Type Of Reactors Used and Choice Of Enzymes In Biocatalysismentioning
confidence: 99%
“…The operational stability of the enzyme was tested to determine the long-term use of the enzyme. The formation of the MAG product remained stable even after 192 h of continuous operation (6 h for each reaction), 32 consecutive cycles …”
Section: Type Of Reactors Used and Choice Of Enzymes In Biocatalysismentioning
confidence: 99%
“…In Brazil, the plant is mainly present in northeastern and mid-western regions, where it has been exploited sustainably for decades [1][2][3][4][5][6]. The oil extract from its fruit is one of the most important products from the tree due to several biological activities [7][8][9][10], such as antioxidant properties [11][12]. Due to these properties, babassu oil is marketed as an important ingredient for different industries, especially for pharmaceutical and food companies in the north and northeast regions of Brazil [13][14][15].…”
Section: Introductionmentioning
confidence: 99%